The role of histone deacetylase inhibitors in patients with relapsed/refractory multiple myeloma. Issue 1 (January 2014) - Hajek, Roman; Siegel, David; Orlowski, Robert Z.; Ludwig, Heinz; Palumbo, Antonio; Dimopoulos, Meletios
Abstract Clinical outcomes for patients with multiple myeloma (MM) have improved substantially since the introduction of novel agents including the proteasome inhibitor bortezomib and the immunomodulatory drugs thalidomide and lenalidomide. However, most patients with MM eventually relapse, and prognosis remains poor among patients with relapsed and/or refractory disease. Combination therapy using agents with different mechanisms of action is emerging as an attractive treatment approach in oncology to increase efficacy and/or overcome resistance to standard treatment regimens. This review discusses unmet needs in the treatment of MM and the development of histone deacetylase inhibitors as a treatment modality for MM.